A cross sectional survey of international horse-racing authorities on injury data collection and reporting practices for professional jockeys - O`Connor, S.; Hitchens, P. L.; Bolwell, C.; Annan, R.; McGoldrick, A.; Fortington, L. V. (Journal of Equine Veterinary Science, 2021)
Jockey injuries are common in professional horse-racing and can result in life-threatening or career-ending outcomes. Robust injury data are essential to understand the circumstances of injury occurrence and ultimately identify prevention opportunities. This study aimed to identify jockey injury surveillance practices of international horse-racing authorities (HRAs) and the specific data items collected and reported by each HRA. A cross-sectional survey of representatives (e.g. Chief Medical Officer) from international HRAs was conducted. An online and paper questionnaire was designed comprised of 32 questions. Questions considered the barriers and facilitators to data collection within each HRA, and where available, what data were collected and reported by HRAs. Representatives from 15 international racing jurisdictions were included, of which 12 reported collection of race day injuries or falls, using varied definitions of medical attention and time loss. Six HRAs did not have a definition for a jockey injury, and eight HRAs had no parameters for describing injury severity. Race day exposure was collected by two HRAs. Results were commonly presented by HRAs as the number of injuries (n = 9/15) or proportion of injured jockeys (n = 6/15). The lack of a designated role for collection, collation and reporting of data was the main barrier for injury surveillance. Twelve HRAs agreed that mandatory collection would be a strong facilitator to improving practice. Enhancement and standardization of international jockey injury surveillance is required to move forward with evidence informed prevention. Concurrent investigation of how reporting practices can be best supported within existing HRA structures is recommended.